Teacher Training and Development in Thailand - Jamjuree, Danulada (Journal of Research and Curriculum Development, 2018)
Abstract This paper is focused on the transition of teacher education and professional development in Thailand, including both pre-service and in-service teachers. The transition of teacher education in Thailand can be divided into 4 eras: before the Teacher Act 1945, the dawn of the professional teacher(1946-1979), time for thought and effort(1980-1998), and golden age of teachers(1999-present).Pre-service teacher training, key changes included a longer pre-service teacher education program (from a 4 to a 5 years), and a teacher certification system. A professional license may be acquired when finish the course and the assessment criteria is met. In-service teacher training has two main issues: first, to allow all teachers to access a thoroughly developed system. Secondly, various teacher professional development models that meet the needs of teachers with efficiency and effectiveness to enhance the performance of teachers through the development of needs to be used in a diversity of classroom situations.